2019
DOI: 10.1080/02723638.2019.1698865
|View full text |Cite
|
Sign up to set email alerts
|

Reproducing spatial inequality? The sustainability fix and barriers to urban mobility in Portland, Oregon

Abstract: We explore how the language of "just sustainability" may become subsumed into a sustainability fix strategy, depoliticizing the utility of concepts such as justice and/or equity. Building from critical GIS insights, we combine digitized spatial data from participatory mapping exercises and community-organization-based focus groups in Portland, Oregon, regarding a proposed six-mile biking and walking path around downtown. We find that 80% of participants' typical travel destinations are outside of downtown Port… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…While the full community plan was not adopted, key elements of it were, and the participants were able to leverage this success in later processes (Marcantonio and Karner 2014). In the Bay Area case, as in others, residents or community groups partner with academic institutions or public agencies for funding and/or to perform the analysis (Aimen and Morris 2012; London et al 2018; Mahmoudi, Lubitow, and Christensen forthcoming). A related avenue involves “citizen science,” whereby residents themselves collect and share data (in collaboration with scientists) to better understand and communicate concerns (Bonney et al 2014; Corburn 2005).…”
Section: Pursuing Transportation Justice: State- and Society-centric mentioning
confidence: 99%
See 1 more Smart Citation
“…While the full community plan was not adopted, key elements of it were, and the participants were able to leverage this success in later processes (Marcantonio and Karner 2014). In the Bay Area case, as in others, residents or community groups partner with academic institutions or public agencies for funding and/or to perform the analysis (Aimen and Morris 2012; London et al 2018; Mahmoudi, Lubitow, and Christensen forthcoming). A related avenue involves “citizen science,” whereby residents themselves collect and share data (in collaboration with scientists) to better understand and communicate concerns (Bonney et al 2014; Corburn 2005).…”
Section: Pursuing Transportation Justice: State- and Society-centric mentioning
confidence: 99%
“…Three recent examples of this type of integrated approach illustrate the promise of hybrid approaches: focusing performance assessments on community-identified groups or geographic areas, interactive mapping/public engagement approaches, and modeling scenarios guided by regional equity ideals. The first approach has not been extensively studied in the literature to date (but see, e.g., Mahmoudi, Lubitow, and Christensen forthcoming). It must be based upon a robust public engagement effort that seeks to identify and address the needs of underserved and disadvantaged communities.…”
Section: Within Through and Beyond The State? The Frontiers And Limmentioning
confidence: 99%
“…Building on the same bikeway development case study in Portland, Mahmoudi, Lubitow, and Christensen (2019) [76] combine digitized spatial data from participatory mapping exercises and focus groups with the community. It is found that most participants' travel destinations are outside of downtown Portland and that participants experience planning and sustainability in a highly localized manner, challenging the equity rationale of the downtown investment.…”
Section: Justice In Sustainable Development and Planningmentioning
confidence: 99%
“…Perhaps the least considered form of equity was recognitional, although it was mentioned or referred to a few times. For example, the Mahmoudi, Lubitow, and Christensen (2019) [76] case study focusing on a bikeway development in Portland described how the traditional top-down planning model used initially to develop the bike path was ahistorical, resulting in a plan that did not recognize and therefore would not benefit historically marginalized neighborhoods. Moreover, in the context of urban agriculture (UA) Stanko and Naylor (2018) [64] say that attempting to promote equity through UA does not address existing or historical injustices, including access to land and other resources and jobs and economic opportunities.…”
Section: Research Objectives 2: Assessing Integration Of Ej and Sustainabilitymentioning
confidence: 99%
“…These changes ultimately reduce the attractiveness of those neighborhoods to city‐directed investment, potential residents, or new business operations, further driving the increase in poverty and reduction in public service quality (Joassart‐Marcelli, Wolch, Alonso, & Sessoms, 2005). Seeking to address the legacy of racist market manipulation and the inherent unequal distribution of power and resources, scholars and activists have engaged in a vigorous discourse around mobility justice incorporating elements of sustainability, bicycling, and health (Behrsin & Benner, 2017; Golub & Martens, 2014; Hoffmann, 2015; Mahmoudi, Lubitow, & Christensen, 2020; Martens, Golub, & Robinson, 2012; Pereira, Schwanen, & Banister, 2017).…”
Section: Introductionmentioning
confidence: 99%